ASSESSMENT OF SOME MECHANICAL PROPERTIES AND MICROSTRUCTURE OF PARTICULATE PERIWINKLE SHELL-ALUMINIUM 6063 METAL MATRIX COMPOSITE (PPS-ALMMC) PRODUCED BY TWO-STEP CASTING (Nigerian Journal of Technology, 2017)
This work investigates some mechanical properties and microstructures of PPS-AlMMC and compares the properties of the composites and those of the aluminium 6063 (AA6063) alloy. Periwinkle shells were milled to particle sizes of 75µm and 150µm and used to produce PPS-AlMMC at 1,5,10 and 15wt% filler loadings using two-step casting technique. The mechanical properties and microstructures of the composite materials were compared with those of the AA6063 alloy. It was observed that the filler distributes uniformly in the matrix due to the two-step casting technique. Improved strength, ductility, hardness and modulus were obtained when the filler was used to reinforce the alloy. However, using a filler of bigger particle size resulted to reduced tensile strength, ductility and toughness of composites. http://dx.doi.org/10.4314/njt.v36i2.14